2016
DOI: 10.12659/msm.898240
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/Lymphocyte Ratio, Serum Endocan, and Nesfatin-1 Levels in Patients with Psoriasis Vulgaris Undergoing Phototherapy Treatment

Abstract: BackgroundPsoriasis is an autoimmune, inflammatory, and chronic disease. Recent studies have evaluated serum endocan and nesfatin-1 levels in patients with inflammatory disorders. The neutrophil-to-lymphocyte ratio (NLR) is an inflammatory marker currently used in many diseases. The aim of the present study was to evaluate NLR, serum endocan, and nesfatin-1 levels in psoriasis vulgaris before and after narrow-band ultraviolet B (NB-UVB) phototherapy treatment and compared to healthy controls.Material/MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…reported that serum endocan levels were increased in patients with psoriasis vulgaris and correlated with disease activity . On the other hand, there is another report describing that serum endocan levels in patients with psoriasis vulgaris are comparable with those in healthy controls . In addition, also in lichen planus, endocan levels are not increased in the sera .…”
Section: Introductionmentioning
confidence: 90%
“…reported that serum endocan levels were increased in patients with psoriasis vulgaris and correlated with disease activity . On the other hand, there is another report describing that serum endocan levels in patients with psoriasis vulgaris are comparable with those in healthy controls . In addition, also in lichen planus, endocan levels are not increased in the sera .…”
Section: Introductionmentioning
confidence: 90%
“…Balta et al [23] identified elevated levels of endocan-1 in psoriasis, which also correlated positively to disease severity. However, this elevation was not replicated by Erek Toprak et al [24], who found no differences in endocan-1 levels between psoriasis patients and controls. This emphasizes that the role of endocan-1 in psoriasis is uncertain and not yet fully explored.…”
Section: Discussionmentioning
confidence: 76%
“…Erek et al evaluated NLR in 88 individuals including 39 patients with psoriasis and 49 healthy controls and reported that the NLR levels were significantly higher in the patients compared to the controls and the narrow-band ultraviolet B (NB-UVB) phototherapy treatment had no effect on NLR. In contrast, although we did not evaluate pre-and post-treatment values, our study had a larger patient population and also evaluated MPV and PLR in our patients (9). Cemil et al evaluated 42 patients with psoriasis and suggested that both NLR and PLR can be effectively used in patients receiving biologic treatment of psoriasis (4).…”
Section: Discussionmentioning
confidence: 91%